Anchor Forces on Coir-Based Artificial Seagrass Mats: Dependence on Wave Dynamics and Their Potential Use in Seagrass Restoration - Villanueva, Raúl; Paul, Maike; Schlurmann, Torsten (Frontiers in Marine Science, 2022)
Seagrasses represent an essential part of the coastal environment and are hence the target of many coastal restoration projects. Artificial seagrass (ASG) mats may facilitate seagrass growth, making them a captivating option for restoration projects. However, little is known about the forces occurring on mats deployed in marine environments and especially on how these forces are transmitted to the anchoring points. Here, we present a study of prototype biodegradable coconut-mesh mats as base layer for ASG meadows and investigate the forces that occur at the anchors. We test the performance of three mesh types under wave forcing using two different anchor configurations without ASG and subsequently test ASG mats of one mesh type under wave forcing and a 4-anchor configuration to assess the effect of the ASG on anchor loading as a function of incident orbital velocities. We found that the mat composition plays a more important role than the number of anchors in anchor load reduction. The anchor forces were 2–4 times higher at front anchors compared to rear anchors, relative to wave propagation direction, and were also considerably higher in that direction compared to the opposite direction. With ASG, the forces increased compared to the highest measured forces without ASG. The forces on the anchors were almost fully dominated by the drag on the ASG based on material properties, ASG reconfiguration and flow conditions. We derive a relation between horizontal orbital velocities and expected forcing on the anchor based on ASG properties and the corresponding area of each anchor and discuss relevant criteria for the design of ASG mats. This should help to assess the loading on anchors deployed for restoration under specific site conditions and chosen materials.